Canine hookworm: correlation between hematological disorders and serum proteins with coproparasitological results - Campos, Diefrey Ribeiro; Perin, Livia Reisen; Camatta, Nayara Campos; Oliveira, Luanna Castro; de Siqueira, Daniele Fassina; Aptekmann, Karina Preising; Martins, Isabella Vilhena Freire (Brazilian Journal of Veterinary Medicine, 2018)
The objective of this study was to correlate the hematologic changes and serum proteins with parasitism by Ancylostoma sp. in dogs. 50 dogs naturally infected with Ancylostoma sp. were used without distinction of sex, from one to six years of age, belonging to the Experimental Chemotherapy Laboratory of Veterinary Parasitology of UFRRJ. Stool samples were collected and these were identified and was carried out egg counts per gram of faeces. Also, blood samples were collected for the realization of the complete blood count and levels of total protein, albumin, and globulin. The results were tabulated and submitted to Spearman correlation test with 5% significance. Of animals evaluated, 42% showed a reduction in the amounts of red blood cells, hemoglobin and hematocrit consequently were anemic. The eosinophilia was observed in 66% of evaluated animals and 28% had hypoalbuminemia. The correlation was found between the parasitism by Ancylostoma sp. and the development of anemia, eosinophilia, and hypoalbuminemia. Therefore, it can be concluded from these results that the parasitism by this nematode causes anemia, eosinophilia, and hypoalbuminemia